2020
DOI: 10.2147/ijn.s259678
|View full text |Cite
|
Sign up to set email alerts
|

<p>3D-HA Scaffold Functionalized by Extracellular Matrix of Stem Cells Promotes Bone Repair</p>

Abstract: Background and Purpose The extracellular matrix (ECM) derived from bone marrow mesenchymal stem cells (BMSCs) has been used in regenerative medicine because of its good biological activity; however, its poor mechanical properties limit its application in bone regeneration. The purpose of this study is to construct a three dimensional-printed hydroxyapatite (3D-HA)/BMSC-ECM composite scaffold that not only has biological activity but also sufficient mechanical strength and reasonably distributed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 42 publications
(54 reference statements)
0
40
0
Order By: Relevance
“…Alternatively silk fibroins have been manipulated in vitro to form biomaterial rolls resembling the appearance of osteons, which enabled not only osteogenesis of human MSC (hMSC) but also the survival and directional growth of neurite processes [ 81 ]. Other examples include the development of bioglass functionalized gelatin nanofibrous scaffolds, which promoted ectopic bone formation in rats [ 64 ], and the use of the BMSC derived extracellular matrix in combination with a 3D-printed HA scaffold to promote strong osteogenic ability and appropriate “tissue-space” structure [ 82 ]. Furthermore, researchers have also suggested bone synthesis can be improved via a biphasic dual delivery scaffold systems [ 83 , 84 ].…”
Section: Skeletal Tissue Regeneration—advancements Over the Last Dmentioning
confidence: 99%
“…Alternatively silk fibroins have been manipulated in vitro to form biomaterial rolls resembling the appearance of osteons, which enabled not only osteogenesis of human MSC (hMSC) but also the survival and directional growth of neurite processes [ 81 ]. Other examples include the development of bioglass functionalized gelatin nanofibrous scaffolds, which promoted ectopic bone formation in rats [ 64 ], and the use of the BMSC derived extracellular matrix in combination with a 3D-printed HA scaffold to promote strong osteogenic ability and appropriate “tissue-space” structure [ 82 ]. Furthermore, researchers have also suggested bone synthesis can be improved via a biphasic dual delivery scaffold systems [ 83 , 84 ].…”
Section: Skeletal Tissue Regeneration—advancements Over the Last Dmentioning
confidence: 99%
“…Synthetic hydroxyapatite is a plastic biomaterial that acts like a scaffold to the neovascularisation, cellular proliferation, fibrovascular growth, osteoid formation and growth of mineralised bone (Pereira-Junior et al 2013). It has osteoconductive properties (Ramesh et al 2018), and can be combined with MSC to promote osteogenic induction (Chi et al 2020). In this study, hydroxyapatite showed the characteristics of a good scaffold, promoting an intense periosteal reaction in association with AAD-MSC.…”
Section: Discussionmentioning
confidence: 83%
“…The mixed application of natural and synthetic polymer materials seems to be a promising solution to solve the problems of mechanical strength [ 71 ], biocompatibility [ 72 , 73 ], and controllable degradation [ 74 ]. But there is still a need for clinicians and technicians to work together to continue to explore new materials and innovative printing methods.…”
Section: Clinical Applicationsmentioning
confidence: 99%